STANDARISASI MUTU: IMPLEMENTASI STANDARISASI MUTU SD MUHAMMADIYAH 15 SURABAYA UNTUK MEWUJUDKAN PENDIDIKAN YANG BERKUALITAS: Penelitian Studi Kasus - Afis, Muhammad Nabil; Vidiyanti; Mohamad Husein Nurullah; Muhamad Tolhani; Adinda Putri Salsabila; Bunga Hermalia; Aliet Noorhayati Sutisno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study discusses the implementation of the Internal Quality Assurance System (SPMI) at SD Muhammadiyah 15 Surabaya (SD Limas) as an effort to realize quality education. SPMI is implemented through the stages of quality mapping, preparation of quality improvement plans, and periodic evaluations, involving the principal, teachers, school committee, parents, and the community. The research method used is descriptive qualitative, with data obtained through in-depth interviews, observations, and document analysis. The results of the study indicate that the implementation of eight national education standards, including graduate competency standards, content, processes, educators and education personnel, facilities and infrastructure, management, and financing make a significant contribution to improving the quality of learning, student character, and school management. With careful planning and consistent implementation, SD Limas has succeeded in creating a conducive and sustainable educational environment. This study recommends increasing human resource capacity, broader collaboration with the community, utilizing technology in quality management, periodic evaluations, and optimizing facilities and infrastructure to support the sustainability of improving the quality of education.